Evaluasi taman terapeutik pada Taman I Gusti Ngurah Made Agung Kota Denpasar - Massie, Alfin Christian; Mayadewi, Ni Nyoman Ari; Astawa, I Nyoman Gede (Jurnal Arsitektur Lansekap; Vol.6, No.2, Oktober 2020DO - 10.24843/JAL.2020.v06.i02.p03, 2020)
Evaluation on Therapeutic Garden in I Gusti Ngurah Made Agung Park at Denpasar City. I Gusti Ngurah Made Agung park is one of the city parks in Denpasar City that has therapeutic facilities provided to support the activities of the people of Denpasar City. Therapeutic park is an open space specifically designed to meet the physical, psychological, social, and spiritual needs of humans as users. This study aims to evaluate the characteristics and design concepts of a therapeutic garden in I Gusti Ngurah Made Agung park. Methods were used for the research are preparation, inventory, analysis, evaluation and synthesis. The results of this study indicate that the therapeutic garden in the park of I Gusti Ngurah Made Agung was still not in accordance with the design criteria according to experts. Therefore, it can be recommended that a garden design that meets the therapeutic garden criteria, includes: a) Official entrance planning; b) Redesigned pedestrian paths that comply with standards; c) Addition of softscape and hardscape with accents; d) Addition of aromatic plants; e) Addition of noise reducing plants; f) Providing pedestrian paths with a variety of textures; g) Additional facilities for security improvements; h) Even distribution of garden elements; i) Addition of local plants and ornamental plants; j) Addition of water element; k) Addition and improvement of facilities for users with special needs; l) Realignment of park space to support park activities.